Semi-quantum key distribution with two classical users - Wu, Wan Qing; Sun, Chen Yang (Frontiers in Physics, 2022)
Semi-quantum key distribution (SQKD) is an important research issue which allows one quantum participant equipped with advanced quantum devices to distribute a shared secret key securely with one classical user who has restricted capabilities. In this paper, we propose a SQKD protocol which allows one quantum user to distribute two different private secret keys to two classical users respectively at the same time. Alice distributes two particle sequences from Bell states to Bob and Charlie respectively. Once the particles have been processed and returned, Alice can simultaneously detect reflected particles by Bob and Charlie based on Bell-state measurement and generate two different raw keys. To enable more participants in sharing keys, this protocol can be extended to the m + 1 party communication scheme by employing m-particle GHZ state. In large-scale communication networks, this extended model significantly reduces the complexity of communication compared to the traditional SQKD scheme. Security analyses show that the presented protocol is free from several general attacks, such as the entangle-measure attack, the modification attack, the double CNOT attack, and so on.